Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2138/am-2021-7856
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carbon phases in Yamato 74123 ureilite to constrain the meteorite shock history

Abstract: The formation and shock history of ureilite meteorites, a relatively abundant type of primitive achondrites, has been debated since decades. For this purpose, the characterization of carbon phases can provide further information on diamond and graphite formation in ureilites, shedding light on the origin and history of this meteorite group. In this work, we present X-ray diffraction and micro-Raman spectroscopy analyses performed on diamond and graphite occurring in the ureilite Yamato 74123 (Y-74123). The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…Further proof for this kind of carbon associations and the formation of micro‐sized diamonds during a shock event was given by Barbaro et al. (2021, 2022) for the Kenna and Yamato 74123 ureilites.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Further proof for this kind of carbon associations and the formation of micro‐sized diamonds during a shock event was given by Barbaro et al. (2021, 2022) for the Kenna and Yamato 74123 ureilites.…”
Section: Introductionmentioning
confidence: 73%
“…(2011) and Barbaro et al. (2020, 2021, 2022), the G‐band Γ G values were corrected for the instrumental peak broadening using the same approach as Barbaro et al. (2020), where a lithospheric diamond of high gem quality was used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5A), indicating that these had achieved sufficiently high temperature during the shock event to complete the thermodynamic transformation. Barbaro et al (50)(51)(52) found nano-and microdiamonds coexisting with nanographite aggregates in ureilite meteorites and estimated 1,200 to 1,300 °C for this phase assemblage. In accordance with these reports, we hypothesize analogous shock T for the Canyon Diablo sample.…”
Section: Discussionmentioning
confidence: 99%